Manganese superoxide dismutase plays an important role in the inflammatory process and predicts disease severity and activity in patients with ulcerative colitis. Issue 6 (1st February 2014) - Ikumoto, Taro; Hayashi, Shinichi; Tomita, Shigeki; Miwa, Shigeharu; Mitomi, Hiroyuki; Fujimori, Takahiro; Imura, Johji
<x xml:space="preserve">Abstract</x> The aim of this study was to investigate the expression pattern of manganese superoxide dismutase (MnSOD) in relation to inflammatory factors in ulcerative colitis (UC) and characterize this enzyme as a newly identified biomarker potentially linked to disease pathogenesis of UC. MnSOD expression was analyzed immunohistochemically in 48 formalin‐fixed and paraffin‐embedded specimens from patients with UC who had undergone endoscopical biopsy. MnSOD expression was observed in vascular endothelium, macrophages, and polymorphonuclear leukocytes within lamina propria of inflamed mucosa. The patients who did not express MnSOD tended to have stabilization of symptoms, but accompanied with status of inflammation. The MnSOD expression pattern was strongly correlated with disease type. MnSOD was expressed in polymorphonuclear leukocytes of all disease types, but cases of chronically counting and exacerbation type had particularly high frequency of immunopositive cells. MnSOD expression in macrophages was frequently observed in cases of symptom remaining type. The cases with MnSOD expression in the vascular endothelium showed a tendency to express in relapse‐remission and exacerbation of symptoms. Immunohistochemical evaluation for MnSOD expression may be useful for predicting disease severity and activity in patients with UC.